Distribution of species and antimicrobial susceptibility in Enterococcus strains of clinical origin - Maribel Josefina Castellano-González; Armindo José Perozo-Mena; Kimberly Gutierrez; Jessica Jimenez; María Urdaneta (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2018)
In order to establish the frequency of isolation of the different species of enterococci, their distribution according to the type of sample and patient care service and determine the antimicrobial resistance, 1,624 strains obtained from bacteriological cultures of patients attended in the Bacteriological Reference Center at the Autonomous Service University Hospital of Maracaibo, during the period January 2010 - December 2015, were analyzed. The most frequent species were E. faecalis (52.46%) and E. faecium (41.38%). The greatest number of strains was obtained from skin and soft tissues samples (54.92%), urine (23.15%) and blood (17.27%). Services with increased frequency of isolation were: hospitalization of adults (47.71%) and pediatric hospitalization (16.38%). It did not find statistically significant association between the specie of enterococci and sample type, or patient care service (p > 0.05). It was detected more resistance in E. faecium than in E. faecalis. The enterococci are acquiring ever greater antimicrobial resistance, and therefore, it is necessary to maintain permanent vigilance over them, perform their proper identification and timely detect resistance, in order to apply preventive measures before these microorganisms cause a greater intrahospital impact.